2021
DOI: 10.2147/vmrr.s318549
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak Investigation and Molecular Detection of Pox Virus Circulating in Sheep and Goats in Selected Districts of West Gojjam and Awi Zones Northwest, Ethiopia

Abstract: Introduction: Sheep and goat pox virus (SGPV) is a systemic contagious disease causing extreme illness and death in small ruminants. Methods: A cross-sectional study was conducted in West Gojjam and Awi zone of Amhara national regional state Northwest Ethiopia, from November 2018 to May 2019 with the objective of pox virus outbreak investigation and molecular detections in sheep and goats (shoats). The study included clinical examinations of lesions, laboratory analysis, and questionnaire survey. Study locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…None of the suspected outbreak reports was further investigated and confirmed, although the clinical presentation reported indicated that SGP is prevalent in the various regions of Uganda. Consistent with previous reports [ 17 , 18 ] there was seasonal variation in the number of SGP outbreaks reported during the study period with the majority of the outbreaks reported during the dry season [June–August] [ 19 ]. Dry seasons are associated with maximum small ruminant flock comingling and disease transmission due to increased animal movement in search of pasture and water [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…None of the suspected outbreak reports was further investigated and confirmed, although the clinical presentation reported indicated that SGP is prevalent in the various regions of Uganda. Consistent with previous reports [ 17 , 18 ] there was seasonal variation in the number of SGP outbreaks reported during the study period with the majority of the outbreaks reported during the dry season [June–August] [ 19 ]. Dry seasons are associated with maximum small ruminant flock comingling and disease transmission due to increased animal movement in search of pasture and water [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 91%